Investigating Masticatory Cycle Parameters and Functional Wear Characteristics in Older Removable Complete Denture Wearers: A Targeted Literature Review - Savvas Kamalakidis; Athanasios Stratos; Dimitrios Tortopidis; Norina Consuela Forna; Vassiliki Anastassiadou (Oral)
Background: Mandibular movement is inherently complex, involving both lateral and vertical components. In older adults, this complexity is compounded by diminished neuromuscular coordination and reduced proprioceptive feedback, often impairing effective mastication. Objectives: This study aimed to review dental literature on the influence of masticatory parameters in the formation of wear facets on acrylic resin denture teeth. Methods: A targeted literature review was conducted, analyzing peer-reviewed studies from 1991 to 2024 through PubMed and Scopus. The review focused on masticatory parameters, age-related neuromuscular adaptations, chewing patterns, and preferred-side denture tooth wear, affecting older adults using complete removable dentures. Results: Mandibular movement characteristics—particularly velocity, duration, and cycle frequency—were found to significantly influence denture tooth wear, often resulting in reduced bite force and masticatory efficiency. Contemporary denture materials demonstrated improved wear resistance, aiding in the regulation of chewing frequency and velocity. These factors are increasingly important as age-related changes impact the stomatognathic system. Notably, wear facets were most prominent on the maxillary first molars, regardless of the occlusal scheme. Conclusions: This review provided a comprehensive overview of existing research, analyzed current evidence, and offered insights into the role of masticatory function and wear characteristics in older complete denture wearers.